Trastorno por déficit de atención con hiperactividad y su bajo rendimiento académico en un niño de 7 años - Navarrete Delgado, Cindy Paola (2019)
The purpose of this case study is better academic performance; through a psychological intervention in the reduction of symptoms characteristic of attention deficit hyperactivity disorder, through the information that has been collected in each of the sessions, the most affected areas were assessed, being the behavioral, emotional and cognitive. Through the execution of an intervention scheme of cognitive behavioral cutting, positive results were obtained in the aforementioned areas, and they were deteriorated, changing their functional ideas, for more adaptive ones, improving the patient's quality of life; and reinforcing emotional and social ties